INVENTARISASI KEPITING AIR TAWAR DI KECAMATAN KAMPAR UTARA KABUPATEN KAMPAR PROVINSI RIAU - Rikhi Riady; Radith Mahatma; Windarti ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Freshwater crab is widely distributed in river, lake, swamp, canal, and pond. Riau Province has many freshwater crabs, however biological information of these organisms are poorly known. This study aimed to understand the freshwater crab types from the Kampar Utara District, Riau Province. Samples from 14 sampling sites, in the Sawah, Sendayan and Sungai Jalau village had been collected from March to April 2013 using bamboo traps and scoop net. There were 178 crabs captured and all of them belonged to a single genus, Parathelpusa. Numbers of crab were obtained from the shallow riverines with numerous aquatic vegetation and no crab caught in the rivers. Based on the results, it can be concluded that the habitat of Parathelpusa in Riau is shallow riverine with dense aquatic vegetation.